Performing episiotomy nowadays and perineal health complications (Research, Society and Development, 2022)
Pregnancy and childbirth are traditionally female activities that accompany the evolution of humanity. Based on this context, the present study aims to review the risks that episiotomy reflects on women's perineal health. This is an integrative literature review carried out through SciELO, LILACS, BDENF and VHL, through the following DeCS: “episiotomy”, “normal childbirth” and “women's health”. Combined with each other by the Boolean AND operator. As inclusion criteria: articles available in full, in Portuguese, Spanish and English, that addressed the theme, in the last ten years (2012-2022). As exclusion criteria: articles that did not address the topic and repeated studies in the databases. A total of 689 articles were found, after a combined search of descriptors and operators, 10 articles were selected to compose the final sample, as shown in the table below. Through the information obtained, it can be considered that the episiotomy continues to manifest itself deliberately.